Perancangan Tekhnologi Pengolahan Limbah Sekam Padi Pada kelompok rampahdone Farm Dalam Mendukung Ketahanan Pangan Pada Masyarakat Desa Wanasigra Kecamatan Sindangkasih - Tirto Madawistama, Sri; Ni’mah, Khomsatun; Heryani, Yeni; Kurniawan, Dian (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Chaff waste which has no economic value will become of high value after being converted into rice bran through the milling process. Rice bran is very much in demand because it provides many benefits. The abundant and abundant availability of husk waste and only being left and burned is of course a problem due to the lack of information on utilizing this waste. By processing rice husk waste, it can be used as animal feed for boiler chicken and free-range chicken rations for residents who have poultry such as chickens. Furthermore, bran which is a by-product of the rice milling process can also be a staple food with high nutritional value. Bran has a high nutritional content, and so far only often used as animal feed can also be consumed with various properties, such as having a high content of B vitamins namely thiamine, niacin and B6 which play an important role in energy production, cardiovascular health and preventing depression It is also considered as a source of natural fiber. In order to be able to utilize the abundant rice husk waste, an appropriate technology design is carried out in processing rice husk waste in the Wanasigra village community into various alternative results of processing this waste to support food security. The results and outputs of community service activities for the food security scheme (PBM-KP) for the Wanasigra Village community, namely residents becoming more independent, residents can maintain the food security of their families, residents and farmer groups gain knowledge through coaching and counseling in utilizing the results from the design of rice husk waste processing technology , providing assistance to target partners to be more independent in processing rice husk waste, food availability, earning additional income for their families. The method used in the service is through counseling, discussion, mentoring and introduction and design of technology to marketing through agricultural experts appointed by external parties. Sales are facilitated by the appointed chairman to distribute to other areas outside the Wanasigra village.